Stranded assets and scenarios - Caldecott, B; Tilbury, J; Carey, C (Smith School of Enterprise and the Environment, 2014)
Scenarios can help investors, firms and policy makers increase the resilience of assets by making them better prepared for inherently hard to predict events. In this high-level discussion paper we review existing scenarios to determine trends and gaps in the literature and propose a general type of scenario that would be most useful for the management of stranded asset risks.